Analysis of BLDC Electric Motor Shaft Treatment Model Using Numerical Method - Endra Dwi Purnomo Endra; Ammiruddin Aziz; Dewi Rianti Mandasari; Lia Amelia; Agus Krisnowo; Cuk Supriyadi Ali Nandar (Majalah Ilmiah Pengkajian Industri, 2022)
This research studies the shaft strength of a BLDC electric motor. A Shaft is one of the components in a rotary engine and functions to transmit power. The design calculation is needed to determine the effect of the strength of the material being treated. The strength analysis of the shaft used FEM (Finite Element Method). The shaft is modeled on the manufacturing design and tested by numerical simulation with Ansys Mechanical 14.5-BRIN commercial license software. The static simulation used a structural statics module with static and dynamic load input. The research method comparing the results of FEM simulations with two different types of materials is determined. Based on the simulation parameters, the selected material types are JIS S45C tempered and AISI 1045 cold-drawn. The simulation results represent the maximum stress (von Mises) and total deformation. The deformation value of S45C tempered material is slightly higher than that of AISI 1045 cold drawn. However, both materials have the same maximum von Mises stress. Keyword: AISI 1045, Cold drawn, Finite Element Method, Shaft, Static Structure, S45C, Tempered.